Pola Pemanfaatan Ruang pada Usaha Berbasis Rumah (UBR) di Klaster Batik Jenggot Kota Pekalongan - Arisngatiasih Arisngatiasih; Mohammad Muktiali (Department of Urban and Regional Planning, Diponegoro University, 2015)
Pekalongan is a city where batik industry grows rapidly. Jenggot Batik Cluster is ranked at the top three of the 11 batik clusters in Pekalongan City. Home Based Enterprise (HBE) is a kind of business activity which highly contributes to the local economy through housing utilization as a business making a place. However, the HBEs in the Jenggot Batik Cluster are facing problems when the functioning of the house is not clearly separated between the shelter and business utilities. The aim of this research is to examine the pattern of in-house space utilization of the HBEs in the Jenggot Batik Cluster. The study conducts qualitative research method to draw an inference from selected nine respondents taken from snowball sampling technique. The analysis is completed by using qualitative descriptive analysis. The results show that the pattern of in-house space utilization for batik printing activities is classified into mixed and separated uses. The former type features a mixed use of shelter and business functions where the business activity is undertaken in the outer part of the house. The separated type provides a clearer space functioning where the working space may locate separately on the front, in-between, or back of the main building. The space utilization in the HBEs relies on the types and working hours of the batik activities.